TOXICOLOGICAL EVALUATION OF TILMICOSIN AFTER INTRAMUSCULAR INJECTION IN BROILER CHICKEN - M. A. Rasheed; M. Ashraf; A. Javeed; A. A. Anjum (Journal of Animal and Plant Sciences, 2018)
Cardiotoxic effects are more obvious with injectable dosage forms of tilmicosin. This study was designed to evaluate the toxicity of tilmicosin in broiler chicken after intramuscular injection. Seventy chicks were divided into seven groups. Group A was kept as control while groups B, C, D, E, F and G were administered tilmicosin at dose of 6.25, 12.5, 25, 50, 100 and 200mg/kg BW intramuscular for three days. Mortality was recorded. The birds treated with 6.25, 12.5, 25mg/kg of tilmicosin survived, while birds treated with 50, 100 and 200mg/kg died during first 30 minutes of injection. Serum samples were analyzed biochemically using spectrophotometer. A significant increase in levels of ALT, AST, total bilirubin, creatinine, blood urea nitrogen and decrease in levels of ALP, total protein and albumin was seen in groups treated with 12.5 and 25mg/kg of tilmicosin. Tilmicosin at 25mg/kg exhibited mild to severe lesions on liver, kidney and heart respectively. The birds treated with 50,100 and 200mg/kg of tilmicosin showed lesions on heart. Results were analyzed using two-way ANOVA followed by Bonferroni post analysis test. Tilmicosin elicited no significant alterations in biochemical and histopathological parameters at doses 6.25, 12.5mg/kg while mild alterations were observed at dose 25mg/kg. The 50, 100 and 200mg/kg doses of tilmicosin exhibited no change in the histopathological parameters of liver and kidney while changes were seen on heart. It is concluded that tilmicosin should be used intramuscular with care in therapy for not more than three days. by Mycoplasma gallisepticum infection in chickens
Keywords: Tilmicosin; toxicity; in vivo; biochemical; histopathological.